The eye of Horus - McGrath, Peter (House of Anubis, 2012)
"House of Anubis" is a suspenseful live-action show on Nickelodeon and TeenNick that follows eight students at a British boarding school as they make friends and enemies, fall in love--and race to solve a mystery involving an ancient Egyptian curse.